THE PROSPECTS AND CHALLENGES OF DOING MISSIONARY WORK IN CONTEMPORARY NIGERIAN SOCIETY - Abu, Joseph (Studia Theologica Varsaviensia, 2025)
The culture of the contemporary time is undoubtedly a technologically and scientifically based culture. Now and again, we witness a growing dynamism characterized by societal sophistication leading to an excessive emphasis on rationality with a distinct lack of faith. There seems to be a paradigm shift in the notion, understanding, and practice of religion today as it is gradually being eased out in many parts of the world. Religion, once a ‘teacher’, is now a ‘student’ contending for a seat in the ‘classroom of human affairs’. In the face of these social changes, the Catholic Church has remained a sign and a sacrament to the world. It is the moral voice that refuses to conform to worldly standards. Its mission has consistently remained the same, following the eternal plan of the Father, that the Church on earth is missionary by its very nature and has its origin in the mission of the Son and the Holy Spirit. If the mission of the Church in the world is to attain full realization, evangelization must constitute its truest and deepest identity. The church in Nigeria in union with the Universal Church has that important mission of spreading the gospel of Christ. Like any other institution, the Nigerian church faces multi-dimensional and multi-faceted challenges such as religious tensions, ethnic conflicts, insecurity and poor governance, youth underdevelopment and unemployment, syncretism, hedonism and so on. However, its growing receptiveness to the gospel of Christ as laid by the early evangelizers has provided a veritable roadmap for attaining the Church’s overall mission: the salvation of souls. This presentation seeks to underscore the prospects and challenges of doing missionary work in contemporary Nigerian society with particular reference to the proclamation and propagation of the Christian faith to guarantee its steady growth and future expansion. This paper shall as well proffer some practical recommendations which can aid the Nigerian church maintain its relevance and identity amidst conflicting values and societal sophistication.